Spatio-temporal analysis of livestock composition and milk production trends in Himachal Pradesh India: a District-wise analysis - Khalandar S; Ravinder Sharma; Rohit Bishist; MUNIANDY SIVARAM; Subhash Sharma; ARNAB ROY; Krishan Lal Gautam (Indian Journal of Animal Sciences, 2022)
Himachal Pradesh State encompasses total livestock population of 4.41 million in the year 2017, of which 55 % encompasses of bovine and 40.8 % encompasses of ovine population to total livestock population. District-wise trend analysis was performed from the year 2003 to 2017. The population of indigenous cattle has declined by 20.50 %, the population of crossbred cattle is increased by 20.73 % but the buffalo population was remained almost constant and the population of ovine was declined by 6.41 %.  The milk production in year 2018 accounted for 1460.33 metric tone and milk productivity 1.91, 4.72 and 3.38 kg per day from Indigenous, crossbred and buffalo respectively. The milk production increased by 2.28 %, 7.30 % and 3.85 % from indigenous cattle, crossbred cattle and buffalo respectively. The increased milk production in the state was mainly due to shift from indigenous cattle to crossbred dairy animals across state and increase in Lactating efficiency (LE). The predicted milk production in the state will be 1941 MT by 2030. The lactating efficiency of crossbreed occupied highest among the livestock in the Himachal with 51 per cent. Moreover the shift in  growth rate of milk production would be in favor of crossbred rather than indigenous cattle  and buffalo due to observed CAGR and LE trends in past. Therefore the favorable conditions including required infrastructure facilities such as subsidies, Higher AI centers, veterinary clinics and market access should be created for promoting crossbred cattle’s in Himachal Pradesh for the benefit and advancement of the dairy sector.